Transformasi Strategi Komunikasi Humas dalam Mitigasi Krisis Iklim di Indonesia - Valdez Dwi Hapsah Oktavianey; Elsa Finda Rahmastuti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The climate crisis in Indonesia is no longer confined to scientific data; it has evolved into a tangible threat to socio-economic life. The Public Relations division of BMKG (the Meteorology, Climatology, and Geophysics Agency) is therefore compelled to shift its communication strategy from the mere dissemination of technical data toward proactive narratives that foster public awareness and participation. This study employs a literature review that synthesizes perspectives from communication sociology and constructive journalism within the context of climate crisis communication. The findings indicate that climate-related messages often lack resonance in Indonesia’s mainstream media, necessitating reframing to align with the logic of social systems. Accordingly, public relations practitioners must act as agents of change who bridge climate science and lived social realities through a more human-centered communicative approach. The strategic implication lies in adopting solution-oriented constructive journalism that can enhance audience self-efficacy and stimulate collective action in climate mitigation. This study recommends integrating the precision of scientific data with emotionally grounded narratives such as highlighting the disappearance of Papua’s perennial snow as a symbolic case to evoke public urgency and empathy before climate impacts become irreversible.